Migration, Gender and the Political Economy of Care: The Exclusion of Migrant Domestic Workers and the Limits of Civic Nationalism in Taiwan - Allouache, Yannis-Adam (Université d'Ottawa / University of Ottawa, 2017)
My thesis asks why Taiwan does not facilitate a path to citizenship to recent immigrants, despite the obvious advantages to do so, as the government’s attempt to promote its society as a model of civic nationalism in Asia, in relation to the pressing need to address labour shortages caused by population aging. I argue that the political economy of care provision that seeks to address the latter problem trumps concerns over national identity. I will look at the changes in the supply of labour in the sector of care since the 1990s as the evidence. Taiwan illustrates the case of East Asian nations’ rapid transition to post-industrial societies, which are now confronted with acute socio-demographic and care crises stemming from aging populations, low fertility rates and a traditional reliance on the family to provide social welfare. This thesis argues that this change in the supply of labour represents a key indicator of the multiple dimensions of the question of exclusion faced by migrant domestic workers in Taiwan. Civil society actors promoting Taiwan’s civic nationalism in the feminist and labour movements and in a few religious associations are unable to address the rights of foreign live-in caregivers because of the dynamics of the political economy of care in Asia and its dependence on migration for reproductive labour.
Keywords: Taiwan; Migrant Workers; Political Economy of Care; Civic Nationalism